Degradasi Rhodamin B Menggunakan Katalis TiO2-N dan Oksidator Hidrogen Peroksida - Cika Dania Marca; Rahadian Zainul (Departemen Kimia FMIPA UNP, 2022)
This research studies the degradation of rhodamine b with oxidator of hydrogen peroxide and determine how much time the optimum degrade rhodamin b as well as the percent degradation using the photocatalytic method. The photocatalyst used for degradation is TiO2-N 8%. The degradation was carried out with variation the concentrations of hydrogen peroxide 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% and 50% and the variation of irradiation time is 30, 60, 90,120, 150, 180, 210 and 240 minutes. Result of degradation analysed using UV-Vis spectrophotometer. The result showed that the greater the concentration of hydrogen peroxide added, the greater the percentage degradation of rhodamine b. The highest percentage degradation was obtained at 90,26% at the addition of hydrogen peroxide concentration 50% and the optimum time to degrade rhodamin b was 210 minutes with 86,5% degradation percentage with the addition of hydrogen peroxide.